Cyclization of substitued 2-(2-fluorophenylazo)azines to azino[1,2-c]benzo[d][1,2,4]triazinium derivatives - Jankowiak, Aleksandra; Obijalska, Emilia; Kaszynski, Piotr (Beilstein Journal of Organic Chemistry, 2013)
Light-induced cyclization of several substituted 2-(2-fluorophenylazo)azines in the presence of Ca2+ ions to the corresponding triazinium derivatives is investigated experimentally and computationally. The azo derivatives of 4-methylpyridine 4 undergo facile cyclization to the corresponding triazinium 1, and the rate of cyclization increases with increasing number of fluorine atoms at the benzene ring. No triazinium ions were obtained from azo derivatives of 4-cyanopyridine, pyrazine and pyrimidine, presumably due to their instability under the reaction conditions. The experimental results and mechanism are discussed with the aid of DFT computational results.
Keywords: DFT; heterocycles; mechanism; synthesis